Desenvolvimento de estratégias para melhorar a disponibilidade de fósforo em solos através da fermentação em estado sólido - Rodrigues, Natalia Alvarez (Universidade Federal de São Carlos, 2025)
The growing concern over the environmental impacts of intensive agriculture has intensified the search for sustainable alternatives, such as bioinoculants and biofertilizers. Among these strategies, the use of phosphate-solubilizing microorganisms (PSMs) is particularly promising, as they can reduce dependence on conventional phosphate fertilizers, whose production is associated with significant environmental damage. Solid-state fermentation (SSF) has emerged as a favorable cultivation method in this context, enabling the valorization of agro-industrial residues as fermentation substrates, thereby supporting circular economy principles. Given this scenario, this thesis aimed to investigate biotechnological strategies for producing phosphate biofertilizers via the cultivation of PSMs through SSF. Initially, the study focused on improving the solubilization process of phosphate rocks (PRs) through SSF by optimizing oxalic acid production by the fungus Aspergillus niger. Using sequential experimental designs, several variables were assessed, including substrate composition, sucrose supplementation, and methanol addition. A substrate mixture of sugarcane bagasse and soybean bran (1:1 w w-1) was identified as the most effective for stimulating oxalic acid synthesis. Methanol addition proved to be a key factor in this process, increasing acid excretion threefold. Under optimized conditions - 7% methanol and 5 g of sucrose per kg of dry substrate (d.s.) -, substantial solubilization of Bayóvar, Itafós, and Registro PRs was achieved. Furthermore, the SSF process facilitated the release of organic P from the substrate itself, due to the production of enzymes such as phosphatases and cellulases. For Bayóvar PR, a maximum soluble P release of 12.1 g kg-1 d.s. was observed, corresponding to a solubilization efficiency of 63.8%. Based on these promising results, the process was evaluated in bench scale using a multilayer packed-bed bioreactor (PBB). Although the PBB system showed adequate operational behavior, methanol volatilization likely limited the solubilization efficiency to 24.6%. On the other hand, in situ drying of the fermented solids within the PBB successfully preserved both microbial viability and acid phosphatase activity over a 34-day storage period. Furthermore, greenhouse experiments revealed that substituting 50% of chemical fertilizer with the biofertilizers developed on a lab-scale did not compromise plant performance. Additionally, a different approach using the fungus Trichoderma harzianum was also explored, with a focus on optimize sporulation and enhancing the production of metabolites related to increased P acquisition by plants, such as indole derivatives and flavonoids. Cultivation was performed using beer draff and wheat straw as substrates. After optimization of aeration, proportion of substrates and inoculum size in 0.5 L PBBs, high values were achieved: 1.08 × 10¹⁰ spores g⁻¹ dry matter (DM), 511.3 µg g⁻¹ DM of indole derivatives, and 2.2 mg g⁻¹ DM of total flavonoids. At bench scale (22 L PBB), the system still supported good sporulation (1 × 10⁹ spores g⁻¹ DM) and indole derivative production (688 µg g⁻¹ DM). However, overheating of up to 16.5°C above the optimal temperature (25°C) resulted in significant axial and radial thermal gradients, which notably impaired the production of acid phosphatase and flavonoids. Overall, this work provides significant contributions to the development of phosphate biofertilizers through SSF, identifying both promising strategies and key challenges for future advancement.
Development of strategies to improve phosphorus availability in soils through solid state fermentation
Keywords: Biofertilizantes; Fermentação em estado sólido; Solubilização de rocha fosfática; Microrganismos solubilizadores de fosfato; Biorreator de leito empacotado; Biofertilizers; Solid-state fermentation; Phosphate rock solubilization; Phosphate solubilizing microorganisms; Packed-bed bioreactor; ENGENHARIAS::ENGENHARIA QUIMICA